2015
DOI: 10.1073/pnas.1421237112
|View full text |Cite
|
Sign up to set email alerts
|

Surface biosignatures of exo-Earths: Remote detection of extraterrestrial life

Abstract: Exoplanet discovery has made remarkable progress, with the first rocky planets having been detected in the central star's liquid water habitable zone. The remote sensing techniques used to characterize such planets for potential habitability and life rely solely on our understanding of life on Earth. The vegetation red edge from terrestrial land plants is often used as a direct signature of life, but it occupies only a small niche in the environmental parameter space that binds life on present-day Earth and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 23 publications
0
49
0
Order By: Relevance
“…A promising approach in the search for traces of Earth-like life is also focused on the examination of surface and subsurface rock/dust material of meteorites, comets or the nearest Earth neighbors (McKay et al 1996 ; 4/30 Kebukawa et al 2009 ;De Gregorio et al 2013 ). For the remote detection of biosignatures, photosynthetic and non-photosynthetic pigments (Varnali and Edwards 2013 ;Hegdea et al 2015 ;Schwieterman et al 2015 ), biogenic gases from anoxygenic photosynthesis in microbial mats or other biosignature gases (Seager and Bains 2015 ) are new biosignatures of life which have been proposed by researches. One of the strategies for substantiation of the extraterrestrial life existence probability in the Universe is to investigate the stability of selected putative biosignatures in the extraterrestrial analog environments, e.g., within martian simulation chambers or under low Earth orbit in specially designed devices with Marslike atmosphere .…”
Section: Introductionmentioning
confidence: 99%
“…A promising approach in the search for traces of Earth-like life is also focused on the examination of surface and subsurface rock/dust material of meteorites, comets or the nearest Earth neighbors (McKay et al 1996 ; 4/30 Kebukawa et al 2009 ;De Gregorio et al 2013 ). For the remote detection of biosignatures, photosynthetic and non-photosynthetic pigments (Varnali and Edwards 2013 ;Hegdea et al 2015 ;Schwieterman et al 2015 ), biogenic gases from anoxygenic photosynthesis in microbial mats or other biosignature gases (Seager and Bains 2015 ) are new biosignatures of life which have been proposed by researches. One of the strategies for substantiation of the extraterrestrial life existence probability in the Universe is to investigate the stability of selected putative biosignatures in the extraterrestrial analog environments, e.g., within martian simulation chambers or under low Earth orbit in specially designed devices with Marslike atmosphere .…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation is only one among many surface features life produces on Earth (see, e.g., Kiang et al 2007a, Cockell et al 2009, Huet al 2012, Sanroma et al 2013, Hegde et al 2015. Land plants have been widespread on Earth for only approximately 460 Myr (e.g., Zahnle et al 2007), whereas much of the history of life has been dominated by single-celled microbial life.…”
Section: Surface Biosignaturesmentioning
confidence: 99%
“…Biota on Earth generates a wide range of characteristic reflectivity and colors. To mimic detectable surface reflection features of known life, Hegde et al (2015) measured the spectral characteristics of 137 phylogenetically diverse microorganisms containing a range of pigments, including ones isolated from Earth's most extreme environments. The team used an integrating sphere, which mimics the observing geometry of an exoplanet that is modeled as a Lambertian sphere.…”
Section: Surface Biosignaturesmentioning
confidence: 99%
“…Note the diversity in edge wavelengths caused by absorption at different wavelengths and higher reflectance where pigments are not absorbing. Hegde et al (2015) measured the reflectance spectra from 0.35 to 2.5 µm of pure cultures of 137 microorganisms with a variety of pigments suited to different functions, generating a publically available spectral database (biosignatures.astro.cornell.edu). In general, these authors found that the strongest features (e.g., 'edges') in the ensemble of microorganisms were present in the visible to NIR (> 1.0 µm) range due to pigment absorption.…”
Section: Alternative Reflectance Biosignaturesmentioning
confidence: 99%